2017
DOI: 10.1039/c7ra00160f
|View full text |Cite
|
Sign up to set email alerts
|

Different-sized black phosphorus nanosheets with good cytocompatibility and high photothermal performance

Abstract: As a new kind of two-dimensional (2D) material, black phosphorus (BP) has attracted explosive interest in biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 50 publications
0
51
0
Order By: Relevance
“…By combining both the photothermal effect of AuNP and the tumor targeting and magnetic resonance imaging guiding ability of iron oxide nanoparticles, this platform presents enhanced therapeutic effect. Besides surface modification, it has been demonstrated that the size of BP nanosheets also has an important role in their PTT efficiency 131 . Three different sizes of liquid exfoliated BP nanosheets, namely large BP (~394 nm ± 75 nm), medium BP (~118 nm ± 22 nm) and small BP (~4.5 nm ± 0.6 nm) were used to evaluate their PTT efficiency.…”
Section: Biomedical Applications Of Black Phosphorusmentioning
confidence: 99%
“…By combining both the photothermal effect of AuNP and the tumor targeting and magnetic resonance imaging guiding ability of iron oxide nanoparticles, this platform presents enhanced therapeutic effect. Besides surface modification, it has been demonstrated that the size of BP nanosheets also has an important role in their PTT efficiency 131 . Three different sizes of liquid exfoliated BP nanosheets, namely large BP (~394 nm ± 75 nm), medium BP (~118 nm ± 22 nm) and small BP (~4.5 nm ± 0.6 nm) were used to evaluate their PTT efficiency.…”
Section: Biomedical Applications Of Black Phosphorusmentioning
confidence: 99%
“…Under 808 nm laser irradiation for 10 min, nearly all the C6 (glioma cells) and MCF7 (breast cancer cells) cells incubated with 50 ppm of BPQDs for 4 h were killed ( Figure a,b), significantly indicating the obvious photothermal destruction of BPQDs. BP nanosheets with different sizes have also been studied to evaluate their distinct cytocompatibility and capability of photothermal ablation toward cancer cells . It was shown that BP nanosheets with larger size possessed better photothermal ablation of cancer cells.…”
Section: Biomedical Application Of Nano‐bpmentioning
confidence: 99%
“…[97b] The cytotoxicity of BP nanostructures is also size dependent.F or example,t he cytotoxicity of BP nanostructures prepared by vapor growth is lower than that of GO nanomaterials but higher than that of exfoliated transition metal dichalcogenides (TMD) for mammalianc ells. [106] In general, the concentration-, size-, and cell type-dependentc ytotoxicity of BP nanostructures stems from intracellular reactive oxygen species (ROS) and disruption of cell membranes caused by the interactions between BP and cells. [106] In general, the concentration-, size-, and cell type-dependentc ytotoxicity of BP nanostructures stems from intracellular reactive oxygen species (ROS) and disruption of cell membranes caused by the interactions between BP and cells.…”
Section: Nanoscale Black Phosphorusmentioning
confidence: 99%
“…[105] On the other hand, Fu et al have observed that few-layer BP NPs with sizes of 394 AE 75, 118 AE 22, and 4.5 AE 0.6 nm prepared by vapor growth and exfoliated in DMSO all have excellent biocompatibility for different cell lines. [106] In general, the concentration-, size-, and cell type-dependentc ytotoxicity of BP nanostructures stems from intracellular reactive oxygen species (ROS) and disruption of cell membranes caused by the interactions between BP and cells. [102,103] In addition to cytotoxicity,B Pn anostructures are able to induce immune perturbationd epending on the surface conditions.…”
Section: Nanoscale Black Phosphorusmentioning
confidence: 99%